BLOCK STRUCTURE SCHEME OF THE EARTH’S CRUST OF THE TERRITORY OF ARMENIA ACCORDING TO THE COMPLEX GEOLOGICAL GEOPHYSICAL DATA (Proceedings of the YSU C: Geological and Geographical Sciences, 2014)
In this paper were formulated the main unsolved problems of block structure of the territory of Armenia. The new scheme for block structure was built and the classification of those blocks was done. On the scheme of block structure of Armenia three mega blocks and 23 blocks of different classes are separated. As the boundaries of the mega blocks were accepted the deep faults that traditionally are considered as the boundaries among the tectonic zones. The great part of the blocks of first class, with some admissions, are separated more reliable. The boundaries of second classes must be corrected. The main type of movements by the boundaries of blocks during the strong earthquakes is strike-slip.